Proposals for the Second Five Year Plan (1956-61) Government of Madhya Bharat - Planning Commission (Planning Commission, 1955)
The broad objectives of India's Second Five Year Plan, Main in it has been agreed, are (i) a sizeable increase in objectives and I national income so as to raise the level of living in Principles. The country, the aim being to increase the national income by 25 % at the rate of 5 % per annum; (ii) rapid industrialization with particular emphasis on the development of basic industries; (iii) fuller employment, provision being made for creating new employment opportunities for about 10 to 12 million persons; and (iv) social justice, the aim being to establish a socialistic pattern of society. These objectives have been fully kept in view while framing the Second Five Year Plan of the State as it is an integral part of the National Plan. Due consideration has, at the same tine, been paid to the special needs and problems of the State.
Government of Madhya Bharat
Government of Madhya Bharat Planning Department
Keywords: A general appreciation of the Draft State Plan; Review of the program's proposed for different sectors in the State Plan; Summary statement of development expenditure; Employment likely to be generated; abstract of principal materials Required; Machinery and equipment Training of accountants and Subordinate personnel; Amelioration of Backward Classes; Level of Development estimated for 1955-56; Removal of water scarcity; Statistical Organization